Correlation of clinical, cytological and histological findings in oral squamous cell carcinomas - Sousa, Michele Cardoso [UNESP]; Oliveira Alves, Monica Ghislaine [UNESP]; Souza, Luciano Albino [UNESP]; Haberbeck Brandao, Adriana Aigotti [UNESP]; Almeida, Janete Dias [UNESP]; Guimaraes Cabral, Luiz Antonio [UNESP] (Spandidos Publ Ltd, 2014)
The present study aimed to investigate the efficiency of exfoliative cytology by correlating the clinical lesions of oral squamous cell carcinoma (OSCC) with exfoliative cytology and histopathological findings. Cases of OSCC diagnosed between 1984 and 2010 were analyzed. The inclusion criteria for the present study were the availability of detailed clinical findings and a diagnosis of the disease through exfoliative cytology and histopathology. The cases were assessed and assigned scores, which were then submitted to modal expression analysis, which considers the higher frequency scores, thus relating the variables. The cytological findings demonstrated that the majority of the cases had malignant potential. Exfoliative cytology should be used as a supplementary tool for the diagnosis of OSCC, as it enables the early detection of these lesions. However, cytology should not be used as a substitute for histopathological examination.
Keywords: pathology; squamous cell carcinoma; oral cancer; cytology